Pengaruh Model Project Based Learning (PjBL) Terhadap Kemampuan Komunikasi Matematis Siswa SMP Negeri 2 Baubau - Jais, Ernawati; Usa, Suwarni La; Intifadah, Wardah (Jurnal Akademik Pendidikan Matematika, 2024)
The purpose of this study was to determine the effect of the Project Based Learning (PjBL) model on the mathematical communication skills of grade VIII students of SMP Negeri 2 Baubau. This research is a Quasy Experiment research. The population in this study was all grade VIII students in the even semester of SMP Negeri 2 Baubau consisting of 345 students. The research sample was taken using purposive sampling technique , selected class VIII.1 as an experimental class of 22 students and class VIII.4 as a control class of 22 students. The instrument used in this study is a test in the form of an essay. The results of the study are known students' mathematical communication skills in solving statistical problems on the subject of data centering measures. Based on the calculation results using independent samples t test, a calculated value of 2.547 was obtained. For the value of ttable at the level of significance 0.05 (5%) and db = 42 which is 1.681. Based on the calculated value > ttable. So it can be concluded that there is an influence of the Project Based Learning (PjBL) model on the mathematical communication skills of grade VIII students of SMP Negeri 2 Baubau